The benefits of the 5-week Table Stars @school program as part of physical education in primary schools - A pilot intervention study - Irene R. Faber; Johan Pion; Maria W. Nijhuis-Van der Sanden (Universidad de Granada, 2019)
The Table Stars @school program was launched in 2010 to serve as a first introduction to table tennis in primary school children. The main aims of this pilot intervention study were 1. to evaluate the effect of Table Stars @school on the perceptuo-motor skills and selective attention in primary school children in comparison to regular physical education and 2. to find out how many and which children benefited more from Table Stars @school compared to regular physical education. A pilot intervention study was carried out including 177 children between 6 to 12 years from two regular primary schools. All children were tested by means of four perceptuo-motor tests (static balance, walking backwards, speed while dribbling, eye-hand coordination) and a selective attention task (map mission). Both schools were exposed to both the Table Stars @school program and regular physical education in a different order. The results revealed no differences between the regular physical education classes and the Table Stars @school program on group level. However, both interventions showed different responders. Consequently, Table Stars @school seems to fit in as it meets the level of improvement of regular physical education classes and it can be of added value by addressing other children to improve perceptuo-motor skills and selective attention. Nevertheless, intensifying the program and/or integrating it into regular physical education is recommended to increase the effects and better add to the broader development of children.